State policy of ensuring energy security in foreign countries: constitutional and legal aspect - Kukeyev, A.K. (Bulletin of the Karaganda University “Law Series”, 2024)
The article is devoted to the analysis of the state policy of ensuring energy security in foreign countries, which may vary depending on their unique needs, resources and geopolitical position. Many countries import energy resources such as oil and gas. Dependence on supplies abroad can make them vulnerable to political or economic changes in exporting countries. Geopolitical tensions and conflicts can lead to an interruption of energy supplies or even direct conflicts in the energy sector. Climate change can affect energy security through an increase in extreme weather conditions, which can damage infrastructure and energy supplies. Outdated or insufficiently protected infrastructure may be vulnerable to cyber attacks and other threats. Low energy consumption efficiency can increase dependence on imports and worsen energy security. Promoting energy-saving technologies and activities helps to reduce overall energy demand and improve energy efficiency. To address these challenges, countries are developing strategies that include a variety of measures, such as diversifying energy sources, developing energy-saving technologies, diplomatic efforts, improving infrastructure and cyber security, and participating in international organizations and agreements. Each country adapts its policies according to specific circumstances and interests.